Resilience through Cultivation A Sociological Analysis of Home Gardening Practices during the COVID-19 Pandemic in Sri Lanka - S.D.Y. Jayarathne (JURNAL ILMU BUDAYA, 2026)
Using a mixed-method approach that incorporated quantitative survey data and qualitative interviews from 150 randomly selected households, the research explores the social, economic, and psychological dimensions of home gardening during the crisis. The findings reveal that 53% of participants were female and 47% male, with most households initiating or expanding their gardens as a direct response to lockdown restrictions. Approximately 73% identified the pandemic as the primary motivation for cultivating home gardens, while 90% adopted organic fertilizer due to shortages of chemical alternatives. Economically, home gardening alleviated food insecurity and reduced household expenditure, while socially, it fostered community resilience and knowledge sharing through both formal and informal channels. Psychologically, gardening provided therapeutic relief and a sense of purpose during prolonged isolation, contributing to improved mental well-being. The study highlights that 80% of respondents expressed high satisfaction with their gardening experiences, citing self-sufficiency, environmental awareness, and improved dietary quality as benefits.